Emerging Vectors of Narratology: Toward Consolidation or Diversification? (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2013)
This is an introduction to the interviews redacted as a follow-up of the 2013 ENN conference. The discussions that originated at the conference were rich and thought-provoking and so the editors of this special section of «Enthymema» decided to continue the dialogue about the state of the art and the future of narratology.